Grækernes homoseksualitet - Vi er ved at gå til i foucaultisme - Thomsen, Ole (Slagmark - Tidsskrift for idéhistorie, 2018)
In this paper an attempt is made to arrive at a more balanced view of Greek homosexuality. Michel Foucault, in his extremely influential Histoire de la sexualité (1976-1984), depicts the “asymmetric” relationship between a lover (a citizen of, say, 26) and a beloved (a youth of, say, 14) as one of brutal exploitation. The so-called Principle of Isomorphism reigns absolutely here: social inferiority = sexual inferiority. No love, no friendship, no reciprocity. Such is the “love” extolled by Plato and all his idealistic followers. Interpretation of several Greek documents shows this to be unfounded as a universal picture. To demonstrate this is the main purpose of my paper. Any attempt to whitewash Greek homosexuality, this harshly competitive institution, should be resisted, however.